(untitled) (Journal of Legal Studies, 2025)
This paper examines the case for establishing an Independent Fiscal Council in Mauritius as a mechanism to enhance fiscal governance, transparency, and accountability. Despite Mauritius’s reputation as a well-governed small island economy, recurring challenges, including rising public debt-to-GDP ratios (which reached 87% in 2021), persistent budget deficits, instances of public fund misappropriation, and weaknesses in fiscal oversight, indicate the need for institutional reform. Using a mixed-methods approach combining doctrinal legal analysis with comparative research, this study examines primary sources, including legislation and official reports, alongside secondary literature on fiscal governance. The research conducts a comparative analysis of fiscal council frameworks in selected jurisdictions (UK, New Zealand, Brazil, India, Australia, Hungary, Argentina, Luxembourg, and Singapore), drawing lessons applicable to the Mauritian context. The findings demonstrate that Mauritius’s current fiscal governance framework lacks robust independent oversight mechanisms, contributing to fiscal challenges and accountability deficits. The paper proposes a comprehensive model for a Mauritian Fiscal Council, including its legal foundation, institutional design, powers, functions, and relationship with existing institutions, while providing a detailed implementation roadmap addressing the unique political economy challenges facing Mauritius.